Two dimensional numerical analysis of aerodynamic characteristics for rotating cylinder on concentrated air flow - Alias, M. S.; Rafie, A. S. Mohd; Marzuki, O. F.; Hamid, M. F. Abdul; Chia, C. C. (Institute of Physics Publishing, 2017)
Over the years, many studies have demonstrated the feasibility of the Magnus effect on spinning cylinder to improve lift production, which can be much higher than the traditional airfoil shape. With this characteristic, spinning cylinder might be used as a lifting device for short take-off distance aircraft or unmanned aerial vehicle (UAV). Nonetheless, there is still a gap in research to explain the use of spinning cylinder as a good lifting device. Computational method is used for this study to analyse the Magnus effect, in which two-dimensional finite element numerical analysis method is applied using ANSYS FLUENT software to examine the coefficients of lift and drag, and to investigate the flow field around the rotating cylinder surface body. Cylinder size of 30mm is chosen and several configurations in steady and concentrated air flows have been evaluated. All in all, it can be concluded that, with the right configuration of the concentrated air flow setup, the rotating cylinder can be used as a lifting device for very short take-off since it can produce very high coefficient of lift (2.5 times higher) compared with steady air flow configuration.